PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Ika Nova Andriani; Sri Trisnaningsih (Gorontalo State University, 2023)
This study aims to examine the effect of Good Corporate Governance on the financial performance of banking companies listed on the Indonesia Stock Exchange. Good financial performance is used as a benchmark to provide an overview of the success that has been achieved in the success of the business. The population in this study are banking companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research is a quantitative research. This study used a purposive sampling technique. The number of samples in this study were 60 samples. The analysis technique in this study used multiple linear regression analysis. The results showed that institutional ownership and independent commissioners had no effect on financial performance, while managerial ownership and audit committee had an effect on financial performance.